Altering sorption and diffusion coefficients of gases in 6FDA-based membrane via addition of functionalized Ti-based fillers - Suhaimi, N.H. (John Wiley and Sons Inc, 2022)
In this work, we systematically investigate and analyze the transport properties including carbon dioxide and methane gases, as well as carbon dioxide induced-plasticization behavior over 6FDA-based mixed matrix filled with nonfunctionalized and amine-functionalized MIL-125 (Ti) particles. First, the sorption behavior and permeability of CO2 and CH4 gases across the membranes were evaluated experimentally. Then, the dual-mode sorption model was used to determine the gas solubility coefficients of gases, whereas the partial immobilization model was used to quantify the diffusivity coefficients of gases. From the results obtained, the permeability of CO2 and the ideal selectivity of CO2/CH4 increased 86â118 upon the addition of nonfunctionalized and amine-functionalized MIL-125 (Ti) fillers into 6FDA/durene polymer. Such increment was mainly attributed to the altered sorption and diffusion properties of the membrane after incorporating the fillers that promoted the transport of CO2 through the membrane. The coefficients of Langmuir sorption capacity (Câ²H), Henry's law (KD), and affinity constant (b) obtained for NH2-MIL-125 (Ti)/6FDA-durene increased 35.5, 179.8, and 104.4, respectively, compared to pure 6FDA-durene membrane. Besides, NH2-MIL-125 (Ti)/6FDA-durene mixed matrix membrane showed the highest diffusivity coefficient of 35.1 Ã 10â8Â cm2/s, resulting in higher CO2/CH4 selectivity of 37.1. In addition, the CO2 plasticization resistance obtained for nonfunctionalized and amine-functionalized mixed matrix membrane was also improved about 150â200 compared to pure 6FDA-durene membrane. Overall, this study revealed that the inclusion of fillers into the polymer matrix has resulted in higher membrane performance than the neat membrane, which associated with the increased of both diffusivity and solubility of CO2. Thus, the incorporation of fillers into polymer matrix has altered the gas transport behavior, and this study could provide basic information on gas transport properties in analyzing the gas separation performance of 6FDA-based mixed matrix membranes. Â© 2021 Society of Plastics Engineers.